EMOSI POSITIF MEMEDIASI PENGARUH ATMOSFER TOKO TERHADAP PEMBELIAN TIDAK TERENCANA - Artana, I Putu Widya; Aksari, Ni Made Asti (E-Jurnal Manajemen; Vol 9 No 5 (2020)DO - 10.24843/EJMUNUD.2020.v09.i05.p17, 2020)
Unplanned purchases are purchases that are made without going through the planning process. Unplanned purchases are caused by various factors, one example is store atmosphere. A good store atmosphere can generate positive emotions on consumers. This study aims to determine the role of positive emotions in mediating the influence of store atmosphere on unplanned purchases in Alfamart Denpasar. This study used 104 people as samples by using purposive sampling technique. Data in this study were collected through online questionnaires using Google form, and analysed using Path analysis. The results show that store atmosphere has significant influence on positive emotions and unplanned purchases. Positive emotions also have significant effect on unplanned purchases. Furthermore, study results also show that positive emotions can mediate the influence of store atmosphere on unplanned purchases. Keywords: store atmosphere, positive emotions, unplanned purchases.